2020
DOI: 10.3389/fneur.2020.565125
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Asymmetric Vestibulo-Ocular Reflex Responses Following Onset of Vestibular Neuritis Is Similar Across Canal Planes

Abstract: Background: We examined whether, after onset of acute unilateral vestibular neuritis (aUVN), initial disease effects, subsequent peripheral recovery and central compensation cause similar changes in vestibular ocular reflex (VOR) gains in all 3 semi-circular canal planes. Methods: 20 patients, mean age 56.5 years, with pathological lateral canal video head impulse test (vHIT) VOR gains due to aUVN, were subsequently examined with vHIT in all 3 canal planes on average 4.3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The gain asymmetry decreased on the affected side, mainly in the affected AC/unaffected PC plane ( Table 2 ). However, Allum and Honegger [ 20 ] reported that the mean gain asymmetry change between onset and 5 weeks was greater ( p < 0.001) in the horizontal canal plane (from 36.9% to 19.4%) than in the other planes.…”
Section: Discussionmentioning
confidence: 99%
“…The gain asymmetry decreased on the affected side, mainly in the affected AC/unaffected PC plane ( Table 2 ). However, Allum and Honegger [ 20 ] reported that the mean gain asymmetry change between onset and 5 weeks was greater ( p < 0.001) in the horizontal canal plane (from 36.9% to 19.4%) than in the other planes.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PSC was the only hypoactive canal in the contralateral ear in all cases and the expected corrective saccades after head impulses were lacking in most cases, raising the possibility that our findings might be due to artifacts. Nevertheless, most healthy PSCs exhibited highly reduced VOR-gain values compared to ipsilateral SCs also in larger cohorts with unilateral vestibular loss ( 41 ). Moreover, the functional impairment for the PSC of the unaffected ear in the first two cases might reflect the greater effect of aging on PSC VOR-gain compared to the other SCs ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Either the planned approaching trajectory yaw velocity is set by patients with aUVL to a larger preprogrammed yaw velocity than that set by HCs to ensure a collision does not occur, or, the same velocity is set by the subjects with aUVL as set by HCs, but larger velocities result because the feedback vestibulo-spinal gain countering trunk rotation velocities is too strong, that is, destabilizing, or, third, a combination of the effects occur in patients with aUVL. For the vestibulospinal gain explanation to be valid, the equal effect of unilateral vestibular loss on yaw velocities for turning away from the deficit vs. the non-deficit side would be divergent from the clearly asymmetric responses seen in vestibulo-ocular reflexes (Halmagyi et al, 1990;Palla and Straumann, 2004;Allum and Honegger, 2020a). Vestibulo-spinal influences on trunk muscles are inhibitory.…”
Section: Changes In Yaw Movement Strategies and Direct Vestibulo-spin...mentioning
confidence: 98%
“…Walking among crowds trying to avoid colliding with people is described by patients with vestibular disorder as vertigo-inducing. This is one particular situation where 45% of patients with chronic vestibular disorders, as reported by several clinical centers, noted difficulties with ( Whitney et al, 2016 ), presumably for three reasons: First, finely controlled trunk yaw angular rotations of the patients and linear distances to the obstacle are required to avoid bumping into someone ( Vallis and McFadyen, 2003 ; Olivier et al, 2013 ); second, the head and trunk rotate in phase ( Vallis and McFadyen, 2003 ), permitting easier use of the lateral semi-circular canal signals to control trunk velocities; third, compounding the first two reasons because the lateral vestibular semi-circular responses providing yaw control signals are more commonly affected by acute unilateral vestibular neuritis than the vertical canals ( Allum and Honegger, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation